Katerina Maridaki-Kassotaki: In memoriam - Kokkinos, Constantinos M.; Antonopoulou , Aikaterini (Psychology: the Journal of the Hellenic Psychological Society, 2022)
The present article begins with a brief introduction of the papers included in this special issue and then moves on to a thorough discussion of Katerina Maridaki-Kassotaki’s work. It then documents and discusses the latest scientific advancements in the field of research on parenting and children and adolescents development, in combination with the findings of Maridaki- Kassotaki's research studies, while also integrating the outcomes from the articles in the special issue.